Mobile sensor routing for parameter estimation of distributed systems using the parallel tunneling method - Zięba, Tomasz; Uciński, Dariusz (Zielona Góra: Uniwersytet Zielonogórski)
The paper deals with the problem of optimal path planning for a sensor network with mutliple mobile nodes, whose measurements are supposed to be primarily used to estimate unknown parameters of a system modelled by a partial differential equation. The adopted framework permits to consider two- or three-dimensional spatial domains and correlated observations.
Keywords: sensor network; distributed parameter systems; optimum experimental design; tunneling algorithm; parallel computing